Trust and Openness in Visual Communication: An Augmented Reality Analysis - Risa Amalia (Sean Institute, 2025)
Augmented Reality (AR) is a technology that integrates virtual elements into the real world, creating a more immersive, interactive experience. This technology is increasingly used in various fields, including education, business, and communications. This study, entitled